Daniel Tiger's neighborhood. Daniel visits the farm [videorecording (DVD)] (PBS Kids, 2017)
Join Daniel Tiger for some grr-ific farm fun! Daniel rides a horse for the first time with encouragement from Dad Tiger, helps his sister Margaret feed adorable ducks, and plays farm with O the Owl. Have fun with Daniel Tiger as he learns how to help others, conquers his fears, and much more!